Consumer acceptance of patient‐performed mobile teledermoscopy for the early detection of melanoma3. (2nd September 2016) - Horsham, C.; Loescher, L.J.; Whiteman, D.C.; Soyer, H.P.; Janda, M.
Summary: Background: Mobile teledermoscopy allows consumers to send images of skin lesions to a teledermatologist for remote diagnosis. Currently, technology acceptance of mobile teledermoscopy by people at high risk of melanoma is unknown. Objectives: We aimed to determine the acceptance of mobile teledermoscopy by consumers based on perceived usefulness, ease of use, compatibility, attitude/intention, subjective norms, facilitators and trust before use. Consumer satisfaction was explored after use. Methods: Consumers aged 50–64 years at high risk of melanoma (fair skin or previous skin cancer) were recruited from a population‐based cohort study and via media announcements in Brisbane, Australia in 2013. The participants completed a 27‐item questionnaire preteledermoscopy modified from a technology acceptance model. The first 49 participants with a suitable smartphone then conducted mobile teledermoscopy in their homes for early detection of melanoma and were asked to rate their satisfaction. Results: The preteledermoscopy questionnaire was completed by 228 participants. Most participants (87%) agreed that mobile teledermoscopy would improve their skin self‐examination performance and 91% agreed that it would be in their best interest to use mobile teledermoscopy. However, nearly half of participants (45%) were unsure about whether they had complete trust in the telediagnosis. The participants who conducted mobile teledermoscopy ( n = 49) reported that the dermatoscope was easy to use (94%) and motivated them to examine their skin more often (86%). However, 18% could not take photographs in hard‐to‐see areas and 35% required help to submit the photograph to the teledermatologist. Conclusions: Mobile teledermoscopy consumer acceptance appears to be favourable. This new technology warrants further assessment for its utility in the early detection of melanoma or follow‐up. Abstract : What's already known about this topic? Cancer Councils recommend that patients conduct regular skin self‐examinations for the early detection of melanoma. Patient‐initiated, self‐performed mobile teledermoscopy may aid consumers in this process. What does this study add? Older adults at high risk of melanoma are highly accepting of mobile teledermoscopy. However, complete trust in the telediagnosis was a concern among some participants. Most participants found mobile teledermoscopy easy to conduct. Linked Comment: Rossi and Marghoob. Br J Dermatol 2016;175 :1146 . Plain language summary available online